Status rodziny w kontekście rynku medialnego. Przyczynek do dyskusji o etyce mediów - Michalski, Michał A. (Annales. Etyka w Życiu Gospodarczym, 2014)
This article discusses the question of the presence of the category of the family in the media, which most often operate as commercial enterprises these days. At the same time the influence of media communication on the family is underlined. The analysis results in distinguishing between two ways of presenting and treating the family in media broadcasting. The first – objective – resembles the authentic nature and character of this basic social group, while the second – subjective – distorts the image and uses the category of the family as merely material for an producing media offer of any kind. Among other issues, stress is put on the business model of media enterprises, which seriously influences the social communication character of mass media, which results, for example, in the transformation of information into a commodity and the media public into customers.